2018
DOI: 10.1186/s13643-018-0769-7
|View full text |Cite
|
Sign up to set email alerts
|

Protocol for a systematic review of autologous fat grafting for wound healing

Abstract: BackgroundAutologous fat grafting is an emerging therapeutic option for cutaneous wounds. The regenerative potential of autologous fat relates to the presence of adipose-derived stem cells (ADSCs) within the stromal vascular fraction (SVF). ADSCs are capable of differentiating into fibroblasts and keratinocytes, as well as secreting soluble mediators with angiogenic and anti-inflammatory properties. However, to date, there has been no comprehensive assessment of the wound healing literature in humans. This sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 24 publications
0
9
0
2
Order By: Relevance
“…All authors agreed on the study selection criteria during the protocol stage (PROSPERO ID: CRD42017081499). 12 All primary clinical studies using AFG in human subjects for acute or chronic cutaneous wounds (defined as loss of epithelial continuity) of any depth were included. This included randomized controlled and observational studies with ≥3 participants.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All authors agreed on the study selection criteria during the protocol stage (PROSPERO ID: CRD42017081499). 12 All primary clinical studies using AFG in human subjects for acute or chronic cutaneous wounds (defined as loss of epithelial continuity) of any depth were included. This included randomized controlled and observational studies with ≥3 participants.…”
Section: Methodsmentioning
confidence: 99%
“…The protocol for this systematic review was prospectively registered on the International Prospective Register of Systematic Reviews (PROSPERO) (PROSPERO ID: CRD42017081499) and published in full before this review was conducted. 12 …”
Section: Introductionmentioning
confidence: 99%
“…Clinical trials of SVF in the treatment of wound defects are not numerous at the moment. However, there are descriptions of the effects of accelerating neovascularization and epithelialization, as well as of the stabilization of inflammation, in a number of published studies ( 38 - 40 ).…”
Section: Introductionmentioning
confidence: 99%
“…They also release pro-healing growth factors and anti-inflammatory cytokines [15] as well as healing-related peptides such as leptin and adiponectin that together may enhance wound healing [16]. Several studies have shown that autologous fat grafting may show significant healing qualities in different clinical situations such as chronically scarred tissue after radiotherapy [17], chronic wounds [18], arterial ulcers [19], pressure ulcers, and diabetic foot ulcers [20].…”
Section: Introductionmentioning
confidence: 99%